Relationship Among Green Human Resource Management, Green Knowledge Sharing, Green Commitment, and Green Behavior: A Moderated Mediation Model - Khan, Kalimullah; Shams, Muhammad Shahid; Khan, Qaisar; Akbar, Sher; Niazi, Murtaza Masud (Frontiers in Psychology, 2022)
This paper aims to examine the underlying mechanism of the relationship between perceived green human resource management (GHRM) and perceived employee green behavior (EGB). By drawing on Attitude and social exchange theories, we examine green commitment (GC) as a mediator and green knowledge sharing (GKS) as a moderator of the GHRM- EGB relationship. The study employed partial least square structural equation modeling (PLS-SEM) to analyze 329 responses. Data were collected in two time-lags. The empirical results confirmed that GC mediates the relationship between GHRM and EGB. However, the study results found that green knowledge sharing moderated the indirect influence of green human resource management on green behavior via green commitment. This research signifies the effect of green human resource management, green knowledge sharing, green commitment and green behavior on organizations' sustainability and environmental management. Despite the emerging literature on the significance of green practices in organizations for environmental management, no study has examined the moderating role of green knowledge sharing on the indirect effect of GHRM on green behavior via mediating role of green commitment. This research offers valuable insight into environmental management in organizations through green practices and green behavior in organizations